First-principles Study of SF6 Decomposed Gas Adsorption and Sensing on Pt and N Co-doped Graphene - Wu, Dongyue; Zhang, Demin; Chen, Chao; Zhou, Linxi; Liang, Xuehui (Sensors and materials, 2023)
The detection of SF6 insulation gas decomposition components in gas-insulated switchgear (GIS) is essential for assessing the GIS operating status and ensuring equipment safety. In this study, we explored the adsorption of SF6 major decomposition products (SO2, SOF2, and SO2F2) on Pt and N co-doped graphene (PtN3-GN) using density functional theory (DFT) calculations. The adsorption structure, energy, and charge transfer of the three adsorbed gases on the PtN3-GN surface were investigated. Gas adsorption results showed that PtN3-GN has a high adsorption capacity for these gas molecules, and adsorption energies are −2.55, −2.54, and −3.54 eV, respectively. To explore the interaction mechanism between gas molecules and the PtN3-GN structure, the total and partial densities of states of the system before and after gas adsorption were compared and analyzed. PtN3-GN strongly interacts with gas molecules, leading to high orbital hybridization between the Pt dopant and gas molecules. PtN3-GN has good adsorption performance for gas molecules and has good application prospects in GIS decomposition component detection and fault diagnosis.